Competitiveness and investments under emissions trading - Leon Bremer; Konstantin Sommer (Tinbergen Institute, 2022)
We study the effects of the EU Emissions Trading System (ETS) on employment and profits as well as on the investment decisions of Dutch manufacturing firms. Motivated both by sizable differences between firms that are regulated in different phases and by the gradual increase in regulatory stringency, we pay close attention to treatment effect heterogeneity between firms and over time. We use microdata from Statistics Netherlands to apply two difference-in-differences (DiD) estimators: (1) a matched two-way fixed effects regression and (2) a recently developed, more flexible DiD method, designed for staggered treatment and treatment effect heterogeneity. We find that firms that were first regulated in phase 1 and 2 experience temporary employment losses of between 7 to 9% early in the regulation, but we do not find conclusive evidence for changes in profits. Firms that were regulated the earliest reduced their investments throughout all phases.
Keywords: H23; L51; Q52; 330; Emissions trading; Environmental regulation; Staggered Difference-in-Differences; Treatment heterogeneity; Manufacturing